Tirofiban potentiates agonist-induced platelet activation and degranulation, despite effectively inhibiting aggregation - Aguiar Bucsai, Martina; Idel, Christian; Wollenberg, Barbara; Mannhalter, Christine; Verschoor, Admar (Platelets (Edinburgh), 2022)
We aimed to investigate the effects of integrin αIIbβ3 inhibitor tirofiban on hallmarks of platelet activation, degranulation, and aggregation during its use to analyze activated but non-complexed platelets via flow cytometry. To do so, we used washed platelets from healthy human donors. We combined aggregometry, an assay of platelet functionality, with flow cytometry and ELISA to detect and correlate, respectively, platelet aggregation, activation, and granule release. While tirofiban effectively inhibited agonist-induced platelet aggregation (thrombin receptor-activating peptide 6 (TRAP), convulxin (CVX), U46619 and IV.3), the surface expression of P-selectin and CD63 and granule release of RANTES were significantly increased, indicating that tirofiban enhances degranulation, uncoupled from aggregation. The results show that tirofiban alters the activation phenotype of platelets, something that should be considered when using tirofiban to enable flow cytometric analysis of activated but unaggregated platelet suspensions.